Timor-Leste Health Resource Tracking Study - Nixon, Hamish; Bredenkamp, Caryn (World Bank, Washington, DC, 2016)
The Timor-Leste health resource tracking study was undertaken in order to improve the flow of critical cash and in-kind resources to districts and health centers by identifying, and proposing how to relieve, the most critical impediments in the public financial management (PFM) cycle. The study follows these three inputs backwards through every stage of the PFM cycle in order to unearth the pertinent issues that impede the timely and sufficient delivery of inputs to frontline providers. It required the collection of data from a wide variety of sources and the use of diverse methodological approaches, including semi-structured district- and facility level surveys, one-to-one interviews, transaction analysis, document review, and analysis of the government's financial management information system (FMIS). The study findings are presented in detail, together with the supporting evidence and key related recommendations, in chapter one, operating cash, chapter two, fuel budget, and chapter three, vehicle repairs and maintenance. Chapter four presents a set of cross-cutting findings that affect all areas of the goods and service budget.